(3GdMeGSI GdHUQjIs - (3Ydj Hf CHj GdaQL Hf GdMSf, UOQ GdOjf, CHh GdMSf GdHUQj,J (B659 (3g` s
(3ChdgG (B:s
(3hHYO adeG cGfJ GdeLGejY GdTYQjI UbGd GdCPgGf hcGf Gdedc GdfGUQ CHhGdeXaQ jhSa Hf Gdedc GdYRjR dHjHkG HCTYGQ GdYQH JhNjJ aj JMQjQ eLehY eMJh Ydi bdGFO CTYGQge s
(3BNQgG (B:s
(3NGJeI GdcJGH GZaQ dYHO JGH ef RdGJg eG cGf efg aj GdReGf GdChd s
(3GdfSNI HgG MhGTs
(3YdjgG JedcGJ CbOegG SfI (B849(3g`s
(3hYdi ghGeTgG JbjjOGJ efbhdI Yf GdCUd GdPj ofSNJ efgs
(3hYdi GdUaMI GdChdi NW GdTgGH eMehO Hf SdjeGf Hf agO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B319 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B165s
Keywords: (3GdCOHs